Draft Genome Sequences of Four Saccharibacter sp. Strains Isolated from Native Bees - Smith, Eric A. (Microbiol Resour Announc, 2020)
The genus Saccharibacter is currently understudied, with only one described species, Saccharibacter floricola, isolated from a flower. In an effort to better understand the microbes that come in contact with native bee pollinators, we isolated and sequenced four additional strains of Saccharibacter from native bees in the genera Melissodes and Anthophora. These genomes range in size from 2,104,494 to 2,316,791 bp (mean, 2,246,664 bp) and contain between 1,860 and 2,167 (mean, 2,060) protein-coding genes.